Effect of continuing or finishing high-level sports on airway inflammation, bronchial hyperresponsiveness, and asthma: A 5-year prospective follow-up study of 42 highly trained swimmers - Helenius, I.; Rytilä, P.; Sarna, S.; Lumme, A.; Helenius, M.; Remes, V.; Haahtela, T. (Journal of Allergy and Clinical Immunology, 2002)
Background: Mild eosinophilic airway inflammation and bronchial hyperresponsiveness-ie, mild asthma-have been shown to affect a high proportion of endurance athletes. The persistence of airway inflammation, bronchial hyperresponsiveness, and asthma in this population is not known, however, inasmuch as follow-up studies of athletes' asthma have not been performed. Objective: The purpose of this study was to investigate effect of finishing high-level sports on airway inflammation, bronchial hyperresponsiveness, and asthma. Methods: Forty-two elite competitive swimmers, most of them from the Finnish national team (37/42; 88%), were followed for 5 years in a prospective manner. All of the swimmers completed questionnaires and underwent resting spirometry, histamine challenge testing, and skin prick tests at baseline and at follow-up. Twenty-nine swimmers (69%) also gave induced sputum samples on both occasions. Sixteen (38%) of the swimmers had continued their competitive careers during follow-up (active swimmers), but 26 (62%) had stopped competing more than 3 months before the follow-up examination (past swimmers). Results: Bronchial responsiveness was increased in 7 (44%) of the 16 active swimmers at baseline and in 8 (50%) of the 16 active swimmers at follow-up; it was increased in 8 (31%) of the 26 past swimmers at baseline and in 3 (12%) of the 26 past swimmers at follow-up (McNemar test, P = .025). The difference in the change in bronchial hyperresponsiveness between the study groups was significant (likelihood ratio test, P = .023). Current asthma (defined as bronchial hyperresponsiveness and exercise-induced bronchial symptoms monthly) was observed in 5 (31%) of the active swimmers at baseline and in 7 (44%) of the active swimmers at follow-up; of the past swimmers, it occurred in 6 (23%) at baseline and in 1 (4%) at follow-up (McNemar test, P = .025). The difference in the change in current asthma between the study groups was significant (likelihood ratio test, P = .0040). The sputum differential cell counts of eosinophils and lymphocytes increased significantly during the follow-up period in the active swimmers (Wilcoxon signed rank sum test; P = .033 and P = .0029, respectively); in the past swimmers, the sputum differential cell counts of eosinophils tended to decrease during the follow-up period (P = .17), whereas the differential cell counts of lymphocytes did not change significantly. The changes in the sputum differential cell counts of eosinophils between the study groups differed significantly (Mann-Whitney U test, P = .019). Conclusion: In swimmers who had stopped high-level training, bronchial hyperresponsiveness and asthma attenuated or even disappeared. Mild eosinophilic airway inflammation was aggravated among highly trained swimmers who remained active during the 5-year follow-up. Our results suggest that athletes' asthma is partly reversible and that it may develop during and subside after an active sports career. (J Allergy Clin Immunol 2002;109:962-8.)